The Correlation of Event Tourism towards Travel Motivation and Its Impact on Destination Image of Bali - Arcana, Komang Trisna Pratiwi (Journal of Business on Hospitality and Tourism, 2017)
The implementation of Event Tourism is one form of promotion of a destination that combines a variety of products and displayed in the form of festivals, special events, Meeting, Incentive, Convention, and Exhibition Tourism (MICE Tourism) with the aim of providing a personal experience at a destination. Bali that had degraded its destinations image after terrorist attacks in 2002 and 2005 has made various efforts to restore the image by organizing tourism events. Tourism Image Destinations is an essential component in selecting decision by tourists about travel destinations. This research was focusing on the study of the relationship of organizing event tourism in Bali toward tourist motivation. The study was done to 50 respondents during the silent day in Bali in 2016. By using association correlation test or Chi-Square (X2), which was analyzed using the Statistical Package for Social Science (SPSS) version 23 showed that there was a positive correlation of the implementation of tourism event toward travel motivation and its impact in establishing the destination image of Bali Island itself. Pearson Chi-Square line showed the price of p-value was 0.000 < 0.05 or Ho was rejected. So that through this study, Bali local government must continue to improve creativity in encouraging the growth of Event Tourism for the realization of destination image which safe, peaceful, and superior because of its cultural attractions, natural or man-made art. The local government is also expected to pay particular attention to the potential of this special interest market.